Prolonged middle ear development in Rhinella horribilis - Womack, Molly C. (2018)
Despite the benefit of the tympanic middle ear to airborne hearing sensitivity, anurans range in how soon they develop functional middle ears after transitioning to life on land. Previous evi- dence suggested that bufonids had particularly slow middle ear developmental rates, but precise timelines have not yet been published for this family. Here, we provide the first age-verified middle ear development timeline for a true toad species (family Bufonidae). We find that although middle ear development begins during metamorphosis in Rhinella horribilis, the middle ear remains incomplete 15 weeks after the transition from aquatic tadpole to land-dwelling toadlet. Using this new middle ear timeline, we discuss commonalities and differences in middle ear development among bufonids, as well as among Anura.